A cross-sectional study of impaired glucose tolerance amongst undergraduate medical students - Singh, Kavisha; Malgaonkar, Aniruddha A.; Samel, Dinesh R. (International Journal of Research in Medical Sciences, 2016)
Background: Diabetes is an important chronic disease both in terms of prevalence and associated morbidity and early mortality. Mortality rates in diabetics are two- to threefold higher than those without diabetes. Type 2 Diabetes Mellitus is preceded by a period of abnormal glucose homeostasis and hence early diagnosis is important in decreasing this morbidity and mortality. The oral glucose tolerance test (OGTT) is currently the gold standard for the diagnosis of diabetes. Methods: This cross sectional single observer study was conducted amongst all the undergraduate students and interns of a municipal medical college to assess the point prevalence of impaired glucose tolerance and the factors predisposing to the same. After necessary permissions, participants giving written informed consent were interviewed and participants were subjected to an oral glucose tolerance test (OGTT) and their heights, weights were measured. Results: None of the participants had an increased fasting blood glucose but 30 min, 60 min and 90 min post OGTT blood glucose levels were increased in 9 (11.84%) participants and 120 min post OGTT blood glucose was increased in 15 (19.73%) participants. Increase in Body Mass Index (BMI) shows a positive correlation with fasting (r=0.155) and 120 min post OGTT blood glucose (r=0.042). Increase in weekly junk food servings shows a positive correlation with fasting (r=0.014), 90 min (r=0.004) and 120 min post OGTT blood glucose (r=0.009). Conclusions: Impaired glucose tolerance was present in a substantial number of non-diabetic students and had a correlation with BMI, exercise and junk food intake.